Development and evaluation of solid dispersion of spironolactone using fusion method - s, Shamsuddin; Fazil, Mohammad; Ansari, Shahid Husain; Ali, Javed (International Journal of Pharmaceutical Investigation)
Introduction: Solubility and dissolution of a poor water-soluble drug are the two major barriers for formulation scientists in development of drug delivery. Many of the potent drugs do not show the therapeutic effects due to solubility issues but may show toxicity issues when used in high doses. Solid dispersion (SD) technology is an excellent tool for enhancing the solubility and dissolution and hence related bioavailability. Materials and Methods: SD of spironolactone (SPL) was developed using an inert carrier polyethylene glycol 4000 (PEG 4000) by the conventional fusion method and characterized for various characterization parameters. Results: Solubility of pure drug and SD of SPL in water was found to be 23.54 ± 1.75 μg/mL and 61.73 ± 1.26 μg/mL, respectively. The maximum cumulative percentage release from pure drug, SPL marketed product (tablet), physical mixture, and SPL SD at 60 min was 27.25 ± 1.83%, 35.64 ± 3.65%, 47.72 ± 2.45%, and 74.24 ± 3.25%, respectively in 0.1 N HCl. Conclusions: SD of SPL was developed successfully. The solubility of SPL SD was found to be significantly increased (P < 0.05) as compared to SPL active pharmaceutical ingredient (API) and physical mixture of PEG 4000 and SPL. The current study indicated that SD of SPL was a better option for enhancing solubility of a poorly soluble therapeutic agent.
Keywords: Polyethylene glycol 4000 (PEG 4000); poor water solubility; solid dispersion (SD); spironolactone (SPL)